Systematic review protocol examining the influence of surgeon personality on perioperative decision making in abdominal surgery. Issue 2 (3rd February 2020) - Bisset, Carly Nichola; McKee, Tracey; Tilling, Elliot; Cawley, Mary; Moug, Susan
Abstract : Introduction: There is limited published literature exploring how the personality traits of surgeons may influence preoperative decision making, particularly in the context of visceral/abdominal surgery. Multiple validated personality scoring systems exist and have been used to describe surgeon personalities previously. The degree to which each trait is expressed by abdominal surgeons is neither currently known, nor the impact of these traits on postoperative outcomes. The protocol has been written in line with the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols checklist. Methods and analysis: The search strategy has been developed by a Health Scientist Librarian in collaboration with the review team. The search was conducted on 1st October 2019. Database subject headings and text words relating to 'abdominal/general surgeons', 'personality', 'postoperative outcomes' and 'decision making' formed the basis of our literature search strategy; the MEDLINE, EMBASE, PsycInfo and Cochrane databases will be searched. Three reviewers will independently screen and appraise articles, with a fourth reviewer utilised if disagreements arise. A systematic narrative synthesis will be performed, with information presented in text and table format. These will summarise the findings and characteristics of any included studies. Using guidance from the Centre for Reviews and Dissemination, the reviewers will describe the potential relationship and findings between studies using the narrative synthesis. Studies will only be reported if they are felt to have low or mid-levels of bias. Studies felt to display high levels of bias will be excluded. Ethics and dissemination: This study does not require ethical approval. The formal systematic review will be submitted for peer reviewed publication and presented at relevant conferences. The methods may inform future reviews in other surgical specialties regarding surgeon personality. PROSPERO registration number: CRD42019151375.